The Horns of Moses - Jefferson, Lee M. (The Biblical archaeology review, 2023)
Whenever visitors arrive at the Church of St. Peter-in-Chains in Rome, they are struck with the grandeur of Michelangelo’s sculpture of Moses but ultimately are vexed by his appearance. Why does Moses have horns on his head? In our contemporary context, horned figures often represent devils and demons. Most docents or tour guides would […]